1.) Solve the formula for the indicated variable. B=w-z/v for w= 2.) Solve the formula for the indicated variable. B=rw+r, for w The solution is w=___
Right idea NinjaDevo, but you need to take care in the implementation.
Your solution to part 1 is correct only if the questioner meant b = (w - z)/v. If the question is really as written, namely,
b = w - z/v, then one simply adds z/v to both sides to get w = b + z/v.
For part 2 you must divide every term by r, so b/r = r*w/r + r/r or b/r = w + 1; subtract 1 from both sides to get
w = b/r - 1.
1.) Solve for w:
b=w-z/v ---Multiply both sides by v
bv = w-z ---Add z to both sides
bv+z = w ---Flip it around
w = bv+z
2.) Solve for w:
b=rw+r ---Divide both sides by r
b/r=w+r ---Subtract r from both sides
b/r-r = w ---Flip it around
w = b/r-r
Hopefully this makes sence. Basically your just manipulating the problem a little bit to get w = something rather than b = something.
Right idea NinjaDevo, but you need to take care in the implementation.
Your solution to part 1 is correct only if the questioner meant b = (w - z)/v. If the question is really as written, namely,
b = w - z/v, then one simply adds z/v to both sides to get w = b + z/v.
For part 2 you must divide every term by r, so b/r = r*w/r + r/r or b/r = w + 1; subtract 1 from both sides to get
w = b/r - 1.
Thanks Alan,
I see my error for the second question, but could you explain the error for the first one again...?
I just went by the order of operations, so we have
b = w - z ÷ v
bv = w - z
bv+z = w
I believe this is assuming b = w - (z/v)...not b = (w-z)/v
I'm abit confused...further explanation would be appriciated!
We're probably doing a little more on the first one than we need to, ND.......note that we have...
B = w - z/v
Note the "z/v" is just a single term that we can add to the other side
B + z/v = w and this "isolates" w
Does that make sense???
It makes sence to me why you can do it that way, but I'm still just a little confused on why my way is incorrect...
Maybe I'm just overthinking it.